Effectiveness of a tailored medical support to overcome the barriers to education, treatment and good metabolic control in children with type-1 diabetes from ethnic minorities - Iovane, Brunella; Cangelosi, Antonina Marta; Bonaccini, Ilaria; Mastrorilli, Carla; Di Mauro, Dora; Fainardi, Valentina; Chiari, Giovanni; Maltese, Marilena; Caffarelli, Carlo; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2018)
Aim: To analyze the effectiveness of a tailored medical support to help children from ethnic minorities to achieve the same good metabolic control of autochthonous peers with type-1 diabetes (T1D). Methods: Children <10 years of age belonging to ethnic minority (EM) families (Group 1) were compared with autochthonous peers (Group 2) who received the diagnosis of T1D in 2014-2016. The Protocol for minorities included other than the standard protocol: booklets translated in ethnic minority languages; weekly visits at home or at school; family-guides; clinic visits supported by professional interpreters. After twelve months of this approach, parents of ethnic minority children answered a short questionnaire concerning satisfaction about educational tools for diabetes management. Results: From 1st January 2014 to December 31st 2016, 72 children received the diagnosis of T1D at the University Children Hospital of Parma, Italy. Nineteen children belonged to an EM family (26.38%), and were included in the Group 1. Twenty-one autochthonous peers were randomly recruited for the Group 2. T1D was diagnosed at the same mean age in Group 1 (5.2±2.2) and in Group 2 patients (5.7±2.4). Metabolic derangements at diagnosis were more severe in Group 1 than in Group 2 patients. However, patients of both Groups showed a similar decrease in HbA1c levels during the first 3 and 6 months post diagnosis. Patients did not differ in mean insulin doses at discharge and at follow up. The calls to the emergency toll-free telephone number were more numerous from the parents from Group 1 than from the parents of Group 2. Total cost to implement the tailored protocol in Group 1 was higher of 87% compared with the standard protocol used for Group 2 patients. Great majority of parents reported to be satisfied with the provided diabetes education program. Conclusions: The results of this study suggested that children from EM families can achieve the same good metabolic control of autochthonous peers with T1D, providing a cost-effective tailored support to their family members.